Characterization of Kinesin Family Member 2C as a Proto-Oncogene in Cervical Cancer - Yang, Jing; Wu, Zimeng; Yang, Li; Jeong, Ji-Hak; Zhu, Yuanhang; Lu, Jie; Wang, Baojin; Wang, Nannan; Wang, Yan; Shen, Ke; Li, Ruiqing (Frontiers in Pharmacology, 2022)
KIF2C is known as an oncogenic gene to regulate tumor progression and metastasis. However, its pan-cancer analysis has not been reported. In this study, we comprehensively analyzed the characteristics of KIF2C in various cancers. We found that KIF2C was highly expressed and corresponded to a poor prognosis in various cancers. We also found the significant correlation between KIF2C and clinicopathological characteristics particularly in cervical cancer, which is the most common gynecological malignancy and is the second leading cause of cancer-related deaths among women worldwide. KIF2C mutation is strongly associated with the survival rate of cervical cancer, and KIF2C expression was significantly up-regulated in cervical cancer tissues and cervical cancer cells. Moreover, KIF2C promoted cervical cancer cells proliferation, invasion and migration in vitro, and as well increased tumor growth in vivo. KIF2C knockdown promotes the activation of p53 signaling pathway by regulating the expression of related proteins. The rescue assay with KIF2C and p53 double knockdown partially reversed the inhibitory influence of KIF2C silencing on cervical cancer processes. In summary, our study provided a relatively comprehensive description of KIF2C as oncogenic gene and suggested KIF2C as a therapeutic target for cervical cancer.